PERAN JAKSA PENGACARA NEGARA SEBAGAI MEDIATOR DALAM MEMBANTU BADAN PENGELOLAAN PAJAK TERKAIT KASUS PENUNGGAK PAJAK - Depitha Sukmadayanti; Niken Wahyuning Retno Mumpuni (Supremasi Hukum: Jurnal Penelitian Hukum, 2025)
In general, the public perceives prosecutors only within the scope of criminal law, given their predominant role as public prosecutors in criminal cases. However, this study explores another dimension of the role of State Attorneys (Jaksa Pengacara Negara – JPN) in civil and administrative legal matters, particularly in handling tax arrears cases. Taxes, as a primary source of state revenue, require firm legal enforcement against delinquent taxpayers. This research aims to examine the involvement of JPN in the process of tax debt collection. The study employs an empirical juridical method with a statute approach and a case study approach. Data were collected through observation, documentation, and participation in case handling focus group discussions (FGDs). The findings indicate that JPN plays a strategic role as a mediator who facilitates taxpayers’ commitment to fulfilling their obligations through installment payment schemes. This study recommends stronger collaboration between the Regional Revenue and Retribution Management Agency (BPPRD) and the South Lampung District Prosecutor’s Office to enhance monitoring efforts and provide more preventive warnings. Such measures are essential to encourage tax compliance and reinforce the effectiveness of legal enforcement in the taxation sector.